Tsunami deposits and recurrence on a typhoon-prone coast of northern Taiwan from the last millennium. (1st October 2020) - Yu, Neng-Ti; Yen, Jiun-Yee; Yen, I-Chin; Hirakawa, Kazuomi; Chuang, Chao-Ming
Abstract: Widely known for its hazardous history, Taiwan holds valuable records of NW Pacific tsunamis and typhoons. Despite the similarity between tsunami and typhoon deposits, historical accounts enabled the identification of the 1867 tsunami deposit on the northern coast through matching with the record-setting inundation. However, the identification of prehistoric tsunami deposits has been hindered by severe sediment reworking and post-depositional changes produced by the typhoon-prone, tropical, and humid climate. In this study, we investigated the upper Holocene facies and their sediment sources and radiocarbon ages on distal floodplains and rocky backshores of the northern coast, where sediment reworking is less intense. Four decimetre-thick gravelly layers were identified, intercalated with fluvial mud and colluvium. The gravelly layers are composed of beach-derived quartz-rich sand and rounded gravels of the sedimentary basement rocks, longshore-drift andesite and stranded pumice. The remarkable layer thickness, gravel size, and quartz richness were determined to have endured post-depositional changes. The event layers are sharp-based, matrix-supported, and poorly sorted and have recorded scouring, sediment entrainment and rapid fallout of suspension-rich turbulent flows that probably originated with tsunamis. The event layers occur 0.5–0.8 km inland and 3–11.5 m above sea level, matching the 1867 tsunami inundation and wave height, respectively. Radiocarbon dating tied the event layers to the 1867 tsunami and three prehistoric events that occurred in the periods: 1545 to 1810, 1293 to 1414 and 1090 to 1235, representing a recurrence interval of 83–436 years over the last millennium. Highlights: A new geological tsunami record of Taiwan of the last millennium is established. A historical and three prehistoric events occurred at an interval of 83–436 years. Event deposits have endured long-term reworking and post-depositional changes. Reworking is minimised on distal floodplain and gentle rocky backshore. Decimetre-thick layers of gravel- and quartz-rich contents bear high endurability.